The STMIK Palangkaraya Student Satisfaction Index Application Based on National Standards of Higher Education in the Framework of Educational Quality Assurance: STMIK Palangkaraya Student Satisfaction Index Application Based - Ichsan, Mochammad (STMIK Palangkaraya, 2019)
Since 2003 the Directorate General of Higher Education has published the Higher Education Quality Assurance Manual. The book was then supplemented with Best Practices books which included Learning, Curriculum of Study Program, Human Resources, Student Affairs, Infrastructure and Facilities, Academic Atmosphere, Financial Management, Research and Publication, Community Service, and Governance. STMIK Palangkaraya continues to do this in improving higher education quality assurance by improving campus services and facilities and improving the quality of graduates. According to the national standards of higher education based on the regulation of the Minister of Research, Technology and Higher Education (Permenristekdikti) Number 44 of 2015, regarding the national standards of higher education. In this regulation the national standards of higher education cover national education standards, national research standards and national standards of community service. To facilitate STMIK in developing national education standards, the authors took the initiative to help STMIK to improve the standard by making a study entitled